Pemanfaatan Aplikasi Tiktok Untuk Berita Online (Studi Kasus Pada Akun Tiktok @Suaradotcom) - Ma'arif, Mochammad Ihsan; Fakhruroji, Moch; Fathoni, Uwes (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
This online media more or less uses Tiktok social media as a supporting media in disseminating its news, including Suara.com online media. The purpose of this study is to determine the work system of Suara.com media in publishing news through the TikTok social media application in the form of videos. This research method uses a case study method with the aim of emphasizing the exploration of a system limited to one case in utilizing Tiktok media by Suara.com This research uses the constructivism paradigm and the Little Jhon humanistic research approach. Collecting data by conducting interviews. The results of this research resulted in the conclusion that Tiktok as a new media in disseminating information news is one of Suara.com's ways to embrace and increase reading interest in millennials and so that the public is more concerned about information that is publicized and also that @suaradotcom utilizes this Tiktok application to keep up with the times in disseminating news and information.